“«Sowiźrzał» stary zejdzie się w dary” [‘The Old Howleglas is Good for a Gift’]: About the Russian “Sowiest-Drał” and Its Old Polish Ancestor - Grześkowiak, Radosław (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper concerns the Russian novel Sovest-Dral written before 1763, which is an adaptation of the Old Polish text Sowiźrzał. The author proves that the Russian text is based on an undated early-18th-century edition of the fourth redaction of the Polish version. Furthermore, the changes in the Russian Sovest-Dral are compared with those in the Polish 1786 rewriting titled Kulhawiec cały w żartach [‘The Lame One, All in Jokes’].